Memory crash : the politics of history in and around Ukraine, 1980s-2010s - Kasʹjanov, Heorhij Volodymyrovyč, 1961- 1961- (Historical studies in Eastern Europe and Eurasia, 2022)
"This account of historical politics in Ukraine, framed in a broader European context, shows how social, political, and cultural groups have used and misused the past from the final years of the Soviet Union to 2020"--